The reality of investigative journalism in the Arab world (Journal of the College of Basic Education, 2023)
This research came (the reality of investigative journalism in the Arab world): a study in identifying the necessary ingredients to advance the reality of investigative journalism in the Arab world, to shed light on investigative journalism, monitor its reality in the Arab world, and examine the obstacles that hinder the development of this type of journalism in the Arab countries. And identifying the ingredients that provide ways to advance its reality in the Arab world.The research seeks to achieve a number of objectives, including:1- Identifying the nature of investigative journalism, its development, fields, features, and its importance in the life of contemporary societies.2- Shedding light on the reality of investigative journalism in the Arab world.3- Identifying the most important factors facing the process of growth and development of investigative journalism in the Arab world.4- Determining the most prominent elements of the responsibility entrusted to Arab governments, Arab press institutions and the active forces in Arab societies in providing ways to advance the reality of investigative journalism in the Arab world.